2016
DOI: 10.1093/hmg/ddw266
|View full text |Cite
|
Sign up to set email alerts
|

Dmpkgene deletion or antisense knockdown does not compromise cardiac or skeletal muscle function in mice

Abstract: Myotonic dystrophy type 1 (DM1) is a genetic disorder in which dominant-active DM protein kinase (DMPK) transcripts accumulate in nuclear foci, leading to abnormal regulation of RNA processing. A leading approach to treat DM1 uses DMPK-targeting antisense oligonucleotides (ASOs) to reduce levels of toxic RNA. However, basal levels of DMPK protein are reduced by half in DM1 patients. This raises concern that intolerance for further DMPK loss may limit ASO therapy, especially since mice with Dmpk gene deletion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 66 publications
0
32
1
Order By: Relevance
“…However, loss of SIX5 in mice does not produce the neonatal features of CDM, and our analysis failed to detect significant expression differences of either DMWD (log 2 fold change = 0.51; adjusted P = 0.62) or SIX5 (log 2 fold change = −0.05; adjusted P = 1.0) between control and CDM muscle. Furthermore, DMPK is dispensable for normal muscle development and function in mice (Carrell et al 2016), supporting a minimal contribution of haploinsufficiency models to CDM pathogenesis.…”
Section: Mbnl Loss-of-function Models For Cdm Pathogenesismentioning
confidence: 79%
“…However, loss of SIX5 in mice does not produce the neonatal features of CDM, and our analysis failed to detect significant expression differences of either DMWD (log 2 fold change = 0.51; adjusted P = 0.62) or SIX5 (log 2 fold change = −0.05; adjusted P = 1.0) between control and CDM muscle. Furthermore, DMPK is dispensable for normal muscle development and function in mice (Carrell et al 2016), supporting a minimal contribution of haploinsufficiency models to CDM pathogenesis.…”
Section: Mbnl Loss-of-function Models For Cdm Pathogenesismentioning
confidence: 79%
“…The recent development of antisense oligonucleotides (ASOs) directed at knockdown of DMPK 33 raises interesting possibilities for MVRC as a biomarker because DMPK is known to regulate muscle Na 1 /K 1 -ATPase through its interaction with phospholemman. 34 Although recent studies have found skeletal muscle function to be durably unaffected despite ASO-mediated DMPK knockdown in murine 35 and nonhuman primate models, 36 published human data are lacking, and uncertainty still exists regarding the degree to which reduced DMPK levels in tissues contribute to DM1 pathophysiology. 33 Through analysis in changes in parameters such as MRRP and ESN, MVRCs are well placed to track any fluctuations in the RMMP that may arise from ASO administration.…”
Section: Excitability Alterations Common To Patients Withmentioning
confidence: 99%
“…This toxic RNA effect leads to a failure to generate appropriately spliced isoforms of key muscle genes, leading to myotonia and other symptoms of disease. Loss of DMPK function is well tolerated in mouse models (21) and thus nucleotide-based gene-silencing approaches as potential disease-modifying therapy represent an attractive strategy for this disabling disorder (136). The pathogenic basis of DM2 is less clear, but leading candidates include a toxic RNA effect (e.g.…”
Section: Introductionmentioning
confidence: 99%